The power of experimental models for understanding the genetic basis for superior endurance running - Delgado Caceres, M.; Docheva, D. (MOJ Sports Medicine, 2017)
The genetic basis for superior endurance running still remains elusive. The usage of experimental animal models have been shown to be of considerable help understanding in more detail the role and function of single genes. Due to the starling gene homology between mice and humans, mouse knockout technology has great advantages and is fundamental in biomedical research. The development and physiology of the mouse is similar with those in humans, being relevant for the proper study of the musculoskeletal system and therefore important for superior endurance running.